O cinema na história e a história no cinema: pesquisa e criação em três experiências cinematográficas no Brasil dos anos 1990 - Fonseca, Vitória Azevedo da (2008)
Based upon on the historical research procedures of three movies O Velho, a história de Luiz Carlos Prestes (Toni Venturi, 1997), O Cineasta da Selva (Aurélio Michiles, 1997) e Baile Perfumado (Paulo Caldas e Lírio Ferreira, 1996) this thesis analyses the relationships between history and cinema in the contemporary Brazilian History. Our main purpose was to understand the social production of historical representation either in the historical field as in the cinematographic ground. In order to make it possible we treated the historical research procedure as a constituent element of the film representation in movies with historical issue. We avoid the disposition to verify the veracity of the information or the authenticity or the legitimacy of the used sources, usually applied in the historical analysis of this kind of movies. On the other hand, we had rather emphasize the complex procedure of making the film in which participate historical visions, objectives, availability of documents, and a wide rage of factors that may have influenced any creative process. Each of the three movies analyzed was treated according to its declared particularities and the type of production. For this were used the oral history methodology and the analysis of the filmic narrative elements, as well as a referential bibliography on history theory.